Analisa Performansi menggunakan Metode Power Link Budget pada Jaringan FTTH Perumahan Balikpapan Regency Cluster Castaric - Riswanto, Ifandi Rahmad; Ditrinov, Mohammad Iqbal; Utami, Amalia Rizqi (LPPM ITK, 2023)
According to research conducted by Telkom, Telkom has experienced the addition of Indihome users up to 1.01 million users. So the total number of Indihome subscribers reached 8.02 million. The increasing demand for Indihome subscriptions and also the farther the customer's location will be to reach, the longer the Fiber Optic cable used, it is necessary to do a network analysis in that area in order to determine the performance of the fiber optic network to the customer's residence. Furthermore, it is necessary to do a network analysis in that area in order to know the performance of the fiber optic network to the customer's residence. The analysis was carried out after processing the data using the method. The calculation method used is the power link budget. The power link budget determines the distance and number of connections that affect the attenuation of the indihome fiber optic network in the Balikpapan Regency Cluster Castarica Housing Complex. And the conclusion obtained is that the FTTH network in Balikpapan Regency Cluster Castarica can be categorized as feasible for the maximum total attenuation on the network of 27.92009 dB and the customer's farthest distance from OLT/STO is 7.0574 Km which is in accordance with the standard set by ITU-T G.984 as well as the regulations set by PT. Telkom